Educational evidence based interventions for adults with autism spectrum disorders: experimental evidence - Saverio Fontani (Firenze University Press, 2016)
The educational interventions for adults with autism spectrum disorders are a relatively unexplored topic, in the face of numerous studies on the educational intervention models for the child population. In this paper the results of major studies and meta-analysis on the topic are presented and their implications for educational intervention are discussed. Interventi educativi evidence based per adulti con disturbi dello spettro autistico: evidenze sperimentali Gli interventi educativi per adulti con Disturbi dello Spettro Autistico rappresentano un'area relativamente poco esplorata, a fronte di numerosi studi dedicati ai modelli di intervento educativo rivolti alla popolazione infantile. In questo articolo sono presentati i risultati dei principali studi e delle meta-analisi sul tema e vengono discusse le loro implicazioni per l'intervento educativo.